Betrayal: Robin Lockwood # 7 - Margolin, Phillip (New York : Minotaur Books, 2023)
"Robin Lockwood is now a prominent defense attorney in Portland, Oregon but a decade ago, she was a ranked and rising MMA fighter. Her career came to a quick end when she was knocked out and concussed in the first round by Mandy Kerrigan, a much more talented fighter. Now the situation couldn't be more different, with Kerrigan on her last legs, her career nearly over, arrested for the quadruple murder of the entire Finch family...and Kerrigan's only possible friend is the attorney she beat so many years ago. For Robin, it's no simple case: Margaret Finch was a lawyer working for vicious Russian mobsters, and was in the cross-hairs of both the mobsters and the widower of a woman a client killed; her husband Aaron Finch was deeply in debt to a bookie who threatened his life; her son Ryan was the one who sold Kerrigan illegal performance enhancing drugs and was beaten severely by her when Kerrigan failed her drug test. To complicate matters further, the DA that Robin is facing is the man she's just started dating, the first person she's begun seeing seriously after her husband was killed. In a case where the stakes are high and the truth is elusive, where each new fact twists the case in a new direction, there is seemingly no way to win or direction to turn that will leave Robin Lockwood unscathed."--.
new book 2023 winter.
Keywords: Lockwood, Robin -- (Fictitious character) -- Fiction; Mystery and detective stories; Legal; Thriller; Novels; Legal fiction